2017
DOI: 10.1155/2017/8439098
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Mediated Apoptosis and Genotoxicity Induced by Palladium Nanoparticles in Human Skin Malignant Melanoma Cells

Abstract: The present work was designed to investigate the effect of palladium nanoparticles (PdNPs) on human skin malignant melanoma (A375) cells, for example, induction of apoptosis, cytotoxicity, and DNA damage. Diseases resulting from dermal exposure may have a significant impact on human health. There is a little study that has been reported on the toxic potential of PdNPs on A375. Cytotoxic potential of PdNPs (0, 5, 10, 20, and 40 μg/ml) was measured by tetrazolium bromide (MTT assay) and NRU assay in A375 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 31 publications
8
41
0
Order By: Relevance
“…The rGO-Ag nanocomposite induced apoptosis in epithelial ovarian carcinoma cells. 36 The DNA damage and the oxidative stress observed in the present study are in accordance with the findings of Alarifi et al 37 in the human hepatocarcinoma cells for palladium nanoparticles and with Alkahtane 38 in the A549 for indium tin oxide nanoparticles.…”
Section: Discussionsupporting
confidence: 92%
“…The rGO-Ag nanocomposite induced apoptosis in epithelial ovarian carcinoma cells. 36 The DNA damage and the oxidative stress observed in the present study are in accordance with the findings of Alarifi et al 37 in the human hepatocarcinoma cells for palladium nanoparticles and with Alkahtane 38 in the A549 for indium tin oxide nanoparticles.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations are corroborated with a study in which human skin malignant melanoma cells were treated with palladium NPs. The results revealed DNA damage with an increase in caspase‐3 activity after exposure to palladium NPs for 24 and 48 hours (Alarifi, Ali, Alkahtani, & Almeer, ).…”
Section: Discussionmentioning
confidence: 99%
“…A careful study of the toxicological profile and intracellular fate of NPs is crucial to uncover their biomedical potential [28,31,33]. Although there are several studies reported in the literature [1,9,10,13,14,[19][20][21][22][23][24][25][26][27][48][49][50][51][52][53][54], there is a lack of conclusive data about the biocompatibility of PdNPs. The results are rather conflicting, likely due to the high variety of PdNP synthetic protocols, dimensions, shapes, surface capping agents, purity, cellular lines used for toxicity tests, and the variability of experimental conditions.…”
Section: Toxicity Assessment Of Pdnpsmentioning
confidence: 99%
“…Preliminary data suggest that PdNPs possess radical scavenging activity similar to that of natural enzymes, namely catalase (CAT) [14,16], peroxidase (HRP) [3,16,17], and superoxide dismutase (SOD) [14,15], but these studies are limited to a few cases, in a cell-free environment, and do not provide a clear picture of their structure-function relationship [18]. Moreover, despite such interesting features, the biomedical use of PdNPs is still limited, partially due to conflicting data about their toxicity [19][20][21][22][23][24][25][26][27]. In this regard, the presence of synthesis by-products, endotoxins, contaminations, and surface functionalities has a strong influence and could be the reason of the observed toxicity in many reports [28].…”
Section: Introductionmentioning
confidence: 99%